Regional Disparities and Fiscal Federalism in Russia - Dynnikova, Oksana; Kyobe, Annette; Slavov, Slavi (Washington, D.C. : International Monetary Fund, 2021)
This paper examines how regional disparities have evolved in Russia and how Russia's system of intergovernmental fiscal relations is managing these disparities. Regional disparities have fallen over the past two decades but remain relatively high. Socioeconomic outcomes remain worse in lagging regions despite faster growth and convergence in income levels. The twin shocks of COVID-19 and lower oil prices appear to have impacted richer regions disproportionately. Compared to other large countries with federal systems of government, Russia stands out with its high reliance on direct taxes as a revenue source for its regions. Transfers from the federal budget to the regions provide some redistribution by reducing the dispersion in real per capita fiscal spending, but also tend to be associated with lower growth. The Russian fiscal system offers degrees of redistribution and risk sharing of around 26 and 18 percent, respectively-with in-kind social transfers contributing the most. Finally, federal transfers in the aggregate tend to be procyclical and are also fairly unresponsive to shocks to regions' own revenues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Factor Income Distribution; Foreign Exchange; Informal Economy; Underground Econom